Issues associated with the development of transparent oxynitride glasses. Issue 3 (April 2015) - Ali, Sharafat; Jonson, Bo; Pomeroy, Michael J.; Hampshire, Stuart
Abstract: Oxynitride glasses and glass ceramics are increasingly recognized as potential materials in specialist applications in modern industrial sectors. Oxynitride glasses have superior mechanical, rheological and optical properties to their oxide glass counterparts. Properties of these glasses can be tailored by changes in nitrogen content and additions of various alkaline-earth and or rare-earth elements. In contrast to oxide glasses, oxynitride glasses are difficult to prepare which adds to production costs. Furthermore, they contain impurities in the form of elemental silicon and silicides, have poor oxidation resistance in air above their glass transition temperatures and have poor transparency in the visible region. This article reviews the above issues in relation to the potential applications of these glasses.